Sindrom Koroner Akut Setelah Penyemprotan Insektisida: Hubungan yang Diduga dengan Paparan Organofosfat: Laporan Kasus - Nugroho, Hari; Irsan, Istan Irmansyah; Cahyono, Mardani (PT Kalbe Farma Tbk., 2025)
Introduction: Organophosphate is one of the most commonly used insecticides to control vector-borne illnesses. Both organophosphate and biodiesel (commonly used as solvents for outdoor space spraying methods) intoxications have cardiovascular manifestations. Case: A 58-year-old male with a sudden onset of shortness of breath after spraying insecticides 1 hour before admission. On examination, there were no SLUDGEM (salivation, lacrimation, urination, defecation, gastrointestinal distress, emesis, miosis) fndings. Bibasilar rales were present on auscultation, and a 12-lead ECG showed ST elevation in leads V1-V6. There was no preceding chest pain. The patient received oxygen, antiplatelet loading, and insulin therapy for hyperglycemia and was prepared for primary PCI. Diagnostic coronary angiography revealed a mid-LAD total occlusion, and a drug-eluting stent was implanted with fnal TIMI 3 fow. Discussion: Dyspnea has various causes, including organophosphate (OP) poisoning, which may result in cholinergic syndrome, respiratory dysfunction, and life-threatening cardiovascular complications. Early recognition through rapid diagnostic evaluation and timely interventions such as atropine, oximes, and reperfusion therapy in STEMI are essential to improve survival and outcomes. Conclusion: Early recognition and prompt revascularization are critical in STEMI to reduce infarct size and improve outcomes. Organophosphate exposure may be associated with cardiovascular efects, and clinicians should consider acute coronary occlusion in patients with respiratory complaints after insecticide exposure, even in the absence of classical cholinergic signs.